Religionsunterricht im Freistaat Sachsen Lernen, Lehren und Forschen seit 20 Jahren - Hanisch, Helmut 1943-2016; Gramzow, Christoph 1969- (Leipzig Evangelische Verlagsanstalt, 2012)
2012/2013 marks the 20th anniversary of the time when religious instruction became part of the curriculum in the state school system of Saxony. To honor this occasion the editors have gathered essays, journal articles and lectures documenting various stages in the recent history of religious instruction and religious pedagogy in Saxony. The majority of the texts were contributed by Helmut Hanisch, the driving force and creative mind behind the process of establishing religious instruction in Saxony. In their contributions - some of which have been published before, while others are presented here for the first time – the authors take a look at the parameters prevailing in the early 1990s and at the special conditions the school confronted both pupils and teachers with as an unusual place of religious instruction. The book provides didactic access to basic as well as current topics of religious instruction and informs about the main topics of research and teaching in the field of religious pedagogy at the universities of Leipzig and Dresden.
Archivierung/Langzeitarchivierung gewährleistet
Archivierung prüfen
Keywords: Christian Education -- Germany -- Saxony; Christian Education -- Germany (East); Aufsatzsammlung